Au(111)-supported Platinum Nanoparticles: Ripening and Activity. (23rd January 2017) - Wieghold, Sarah; Nienhaus, Lea; Siebel, Armin; Krause, Maximilian; Wand, Patricia; Gruebele, Martin; Heiz, Ueli; Esch, Friedrich
ABSTRACT: The recent spotlight on supported nanoparticles (NPs) has attracted attention in the field of catalysis and fuel cell technology. Supported NPs can be used as model catalysts to gain a fundamental understanding of the catalytic properties at the interface. Here, especially the wet-chemical preparation of platinum NPs in alkaline ethylene glycol is a powerful approach to synthesize stable particles with a narrow size distribution in the nanometer regime. We combine high resolution imaging by scanning tunneling microscopy with electrochemical characterization by cyclic voltammetry to gain insights into the underlying degradation mechanism of supported platinum NPs, paving the way toward a rational design of supported catalysts with controlled activity and stability.